Brazilian Food Reference Guide for Phenylalanine Content: A Study Based on the Perception of PKU Patients and Health Providers - Santos,Bruna Bento dos (2022)
Abstract The mainstay of management of phenylketonuria (PKU) is restriction of dietary phenylalanine (Phe) intake. The present study sought to assess the perception and understanding of health care providers and lay users (patients/family members/caregivers) regarding the national reference database for checking the Phe content of foods, provided by the Brazilian Health Regulatory Agency (Anvisa), whose data are presented in the Table of Phenylalanine Content of Foods (TCFA-Anvisa) and recently in the Phenylalanine Content of Foods Dashboard (PCCFA-Anvisa); and to identify factors which interfere with the usability of these resources. Two online questionnaires, one for providers (n=33) and another for lay users (n=194), were used to collect sociodemographic information, knowledge about dietary management of PKU, sources of information about the Phe content of foods, and perception and understanding of the Anvisa tools. TCFA-Anvisa and PCCFA-Anvisa were not used as main sources of information by either group. Among the participants who had used these tools (15 providers;35 lay users), most considered the PCCFA-Anvisa to be superior or partially superior to the TCFA-Anvisa. The main limitations reported were related to layout and limited variety of foods. We suggest that the limitations identified in this study be considered for future improvement of these resources.